Human Adipose-Derived Stem Cells Suppress Elastase-Induced Murine Abdominal Aortic Inflammation and Aneurysm Expansion through Paracrine Factors - Xie, Jie (Cell Transplant, 2017)
Abdominal aortic aneurysm (AAA) is a potentially lethal disease associated with immune activation-induced aortic degradation. We hypothesized that xenotransplantation of human adipose-derived stem cells (hADSCs) would reduce aortic inflammation and attenuate expansion in a murine AAA model. Modulatory effects of ADSCs on immune cell subtypes associated with AAA progression were investigated using human peripheral blood mononuclear cells (hPBMNCs) cocultured with ADSCs. Murine AAA was induced through elastase application to the abdominal aorta in C57BL/6 mice. ADSCs were administered intravenously, and aortic changes were determined by ultrasonography and videomicrometry. Circulating monocytes, aortic neutrophils, CD28(−) T cells, FoxP3(+) regulatory T cells (Tregs), and CD206(+) M2 macrophages were assessed at multiple terminal time points. In vitro, ADSCs induced M2 macrophage and Treg phenotypes while inhibiting neutrophil transmigration and lymphocyte activation without cellular contact. Intravenous ADSC delivery reduced aneurysmal expansion starting from day 4 [from baseline: 54.8% (saline) vs. 16.9% (ADSCs), n = 10 at baseline, n = 4 at day 4, p < 0.001], and the therapeutic effect persists through day 14 (from baseline: 64.1% saline vs. 24.6% ADSCs, n = 4, p < 0.01). ADSC administration increased aortic Tregs by 20-fold (n = 5, p < 0.01), while decreasing CD4(+)CD28(−) (-28%), CD8(+)CD28(−) T cells (-61%), and Ly6G/C(+) neutrophils (-43%, n = 5, p < 0.05). Circulating CD115(+)CXCR1(−)LY6C(+)-activated monocytes decreased in the ADSC-treated group by day 7 (-60%, n = 10, p < 0.05), paralleled by an increase in aortic CD206(+) M2 macrophages by 2.4-fold (n = 5, p < 0.05). Intravenously injected ADSCs transiently engrafted in the lung on day 1 without aortic engraftment at any time point. In conclusion, ADSCs exhibit pleiotropic immunomodulatory effects in vitro as well as in vivo during the development of AAA. The temporal evolution of these effects systemically as well as in aortic tissue suggests that ADSCs induce a sequence of anti-inflammatory cellular events mediated by paracrine factors, which leads to amelioration of AAA progression.